2016
DOI: 10.1177/0263775815622211
|View full text |Cite
|
Sign up to set email alerts
|

Feeling precarious: Millennial women and work

Abstract: In Precarious Life (2004), Judith Butler writes about how a shared sense of fear and vulnerability opens the possibility of recognizing interdependency. This is a wider understanding of precarity than is often present in human geography -recognizing the consequences and possibilities of feeling precarious. Focusing on work and the workplace, I examine the working life stories of millennial women in Canada, a labour market where unemployment and underemployment are common experiences for young workers. Using wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…This paper contends that it is important to develop an intergenerational labour geography, and consider affective relationships in particular, as they have a direct influence on our choices and experiences of work and family life. Elsewhere I have argued that as economic actors, the subjective register—how we feel about the choices we make about work—is critical to understanding the labour market more broadly (Worth ). This means paying more attention to how choices that seem to be beyond the labour market are often tied to it intimately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper contends that it is important to develop an intergenerational labour geography, and consider affective relationships in particular, as they have a direct influence on our choices and experiences of work and family life. Elsewhere I have argued that as economic actors, the subjective register—how we feel about the choices we make about work—is critical to understanding the labour market more broadly (Worth ). This means paying more attention to how choices that seem to be beyond the labour market are often tied to it intimately.…”
Section: Resultsmentioning
confidence: 99%
“…Coe and Jordhus‐Lier (2010, 34–35) argue that besides acknowledging that “labour can make a difference, it is time to move one step further and analytically examine and conceptualize the relationships between labour and other social actors.” Labour geography has considered agential relations between workers, the state, and capital, and is now broadening its scope to consider the family and social reproduction (Schwiter et al ). Bringing in a feminist analysis, the edited collections by Mitchell et al () and Meehan and Strauss (2015, 3) highlight how reproductive labour, or “life's work,” enables paid work—and how “the costs of global economic restructuring are ‘downloaded’ onto daily life.” I am interested in the agential choices of workers beyond relations with capital (Worth ), and I have drawn on feminist theories of agency and autonomy that stress our interdependence (Mackenzie and Stoljar ).…”
Section: Context: Making Sense Of Gendered Work Across Generationsmentioning
confidence: 99%
“…Some studies described precarity as including elements of intersubjective life, like housing, and intimate and social relations (Neilson and Rossiter ). Others focused on its objective and subjective dimensions, including ontological insecurity, insecure livelihoods, and social belonging (Butler ; Stewart ; Al‐Mohammad ; Millar ), life trajectories, feelings, and meanings of precariousness and implication of vulnerability (Murgia ; Worth ; Kesisoglou, Figgou, and Dikaiou ; Spini, Bernardi, and Oris ). Recent studies show how the neoliberal economy of globalization has been producing various forms of precarization of labor, livelihoods, and citizenship for migrants (Anderson ; Lewis et al.…”
Section: Precarity Revisited: Socioemotional Relations and Imaginationmentioning
confidence: 99%
“…Nancy Worth (), in her study on the working‐life stories of millennial women in Canada, suggested that interdependency represents a shared condition of precarity. The image of “atomic” individuals participating in the flexible labor market is replaced with relational and interdependent agents who are enmeshed in social networks and who share aspirations and ideas with others.…”
Section: Precarity and Imaginationmentioning
confidence: 99%
“…The concept of precarity has been taken up by scholars and activists to describe both labor and life conditions of vulnerability, risk, and uncertainty that have arisen as employment has shifted toward more casual, insecure, and flexible models in advanced global capitalist countries under neoliberalism (Ross ). In this paper, we consider how precarity shapes daily work and affective experiences of vending (Worth ) for artisan vendors in Ottawa's ByWard Market, as well as how the context of working in a public urban market interacts with and informs these conditions and experiences.…”
mentioning
confidence: 99%